Leptin Promotes Glioblastoma - Johnathan E. Lawrence; Nicholas J. Cook; Richard A. Rovin; Robert J. Winn (Neurology Research International)
The hormone leptin has a variety of functions. Originally known for its role in satiety and weight loss, leptin more recently has been shown to augment tumor growth in a variety of cancers. Within gliomas, there is a correlation between tumor grade and tumor expression of leptin and its receptor. This suggests that autocrine signaling within the tumor microenvironment may promote the growth of high-grade gliomas. Leptin does this through stimulation of cellular pathways that are also advantageous for tumor growth and recurrence: antiapoptosis, proliferation, angiogenesis, and migration. Conversely, a loss of leptin expression attenuates tumor growth. In animal models of colon cancer and melanoma, a decline in the expression and secretion of leptin resulted in a reduction of tumor growth. In these models, positive mental stimulation through environmental enrichment decreased leptin secretion and improved tumor outcome. This review explores the link between leptin and glioblastoma.